Amino acid differences between diabetic older adults and non-diabetic older adults and their associations with cardiovascular function. (September 2021) - Kovalik, Jean-Paul; Zhao, Xiaodan; Gao, Fei; Leng, Shuang; Chow, Vivian; Chew, Hannah; Teo, Louis L.Y.; Tan, Ru San; Ewe, See Hooi; Tan, Hong Chang; Wee, Hai Ning; Lee, Lye Siang; et al.
Abstract: Background: Ageing and insulin resistant states such as diabetes mellitus frequently coexist and increase the risk of cardiovascular disease development among older adults. Here we investigate metabolic differences in amino acid profiles between ageing and diabetes mellitus, and their associations with cardiovascular function. Methods: In a group of community older adults we performed echocardiography, cardiac magnetic resonance imaging as well as cross sectional and longitudinal metabolomics profiling based on current and archived sera obtained fifteen years prior to examination. Results: We studied a total of 515 participants (women 50%, n = 255) with a mean age 73 (SD = 4.3) years. Diabetics had higher alanine (562 vs 448, p < 0.0001), higher glutamate (107 vs 95, p = 0.016), higher proline (264 vs 231, p = 0.008) and lower arginine (107 vs 117, p = 0.043), lower citrulline (30 vs 38, p = 0.006) levels (μM) compared to non-diabetics. Over time, changes in amino acid profiles differentiated diabetic older adults from non-diabetic older adults, with greater accumulation of alanine ( p = 0.002), proline ( p = 0.008) and (non-significant) trend towards greater accumulation of glycine ( p = 0.057) among the older diabetics compared to the older non-diabetics. However, independent of diabetes status, amino acids were associated with cardiovascular functions in ageing, [archived valine ( p = 0.011), leucine (p = 0.011), archived isoleucine ( p = 0.0006), archived serine ( p = 0.008), archived glycine ( p = 0.006) methionine ( p = 0.003)] which were associated with impairments in E/A ratio. Conclusion: Markers of branched chain amino acids and one ‑carbon metabolism pathways were associated with changes in cardiovascular function in older adults regardless of diabetes status. However, nitrogen handling pathways were specifically altered among older adults with diabetes. These findings broaden our understanding into specific amino acid pathways that may be altered between diabetic and non-diabetic older adults, and their relevance to cardiovascular function in ageing. Trial registration: ClinicalTrials.gov Identifier: NCT02791139 Graphical abstract: Unlabelled Image Highlights: Cardiovascular function in ageing is associated with distinct amino acid pathways. Changes in branched-chain amino acids and one carbon metabolism intermediates were associated with left ventricular function in ageing. Nitrogen handling and excretion pathway intermediates were associated with changes in left ventricular and atrial function among older adults with diabetes mellitus.